2015
DOI: 10.1016/j.wear.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of humidity and counter-surface on tribochemical wear of soda-lime-silica glass

Abstract: a b s t r a c tThe effects of counter-surface chemistry on the friction and wear of soda-lime-silica glass were investigated using a ball-on-flat tribometer with various ball materials (stainless steel, silicon nitride, and alumina) in dry and humid environments. It was found that the interfacial wear was very sensitive to environmental humidity and counter-surface chemistry. In dry conditions, soda-lime glass was damaged mechanically regardless of counter-surface materials, creating a rough and deep wear trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…Another way that water can influence the lubricant properties is to change the solubilisation characteristics of the lubricant which results in the desolubilisation of the additive in the lubricant [11]. It was shown that contacting surfaces can be affected in humid conditions by mechanochemical reactions involving the adsorbed water which can be attributed to hydrolysis reactions enhanced by interfacial shear [21].…”
Section: Effect Of Water On Lubricationmentioning
confidence: 99%
“…Another way that water can influence the lubricant properties is to change the solubilisation characteristics of the lubricant which results in the desolubilisation of the additive in the lubricant [11]. It was shown that contacting surfaces can be affected in humid conditions by mechanochemical reactions involving the adsorbed water which can be attributed to hydrolysis reactions enhanced by interfacial shear [21].…”
Section: Effect Of Water On Lubricationmentioning
confidence: 99%
“…In a series of studies under such mechanochemical wear conditions, it was found that sodium calcium silicate (also called soda lime silica, SLS) exhibits a peculiar RH dependence of the mechanochemical wear . While pure silica (fused quartz), alkali borosilicate (Schott Borofloat ® 33), barium boroaluminosilicate (Schott AF45), sodium aluminosilicate (base glass of Corning Gorilla ® 2), and chemically strengthened aluminosilicate (Corning Gorilla ® Glass 2) all show an increase in wear volume as RH increases to >80%, SLS shows a substantial reduction in wear volume at RH >80% compared to the wear at lower RHs . Understanding the origin of the decreased wear of SLS at RH>80% may provide critical insights needed to design and produce SLS glass panels with a superior practical strength.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the glasses whose wear behaviors have been tested, it is noted that only SLS has leachable Na + ions associated with the non‐bridging oxygen (Si–O − ; NBO) atoms in the glass network. This raises questions about the effects of Na + itself in the silicate network vs the structure and reactivity of adsorbed water which may vary with Na + leaching.…”
Section: Introductionmentioning
confidence: 99%
“…Tribo‐corrosion, being a typical mechanochemical behavior, which has been used to explain reciprocating scratch behaviors of glass surfaces in the presence of water. For instance, tribo‐corrosion can be used to explain the damage behavior of silicate glass surfaces in our previous publications, where it was reported that when rubbing with a borosilicate glass (Pyrex) ball, material removal (wear) volume of borosilicate glass would increase as relative humidity (RH) increased from 20% to 90% . Similar behaviors were also found in other glasses, such as fused quartz, barium boroaluminosilicate glass, aluminosilicate glass .…”
Section: Introductionmentioning
confidence: 59%
“…Second, the countersurface can affect the wear behavior of glass significantly. When soda lime glass rubbed with Si 3 N 4 ball, or Al 2 O 3 ball, the wear debris would adhere inside the scratched track of glass substrate . Since the residual energy that ingress into subsurface would be different if these two conditions occurred, the subsurface crack behavior of glass materials can also be different.…”
Section: Discussionmentioning
confidence: 99%